For the Reconstruction of Post-War Italy: The Institutional Transition in the “Cronache Sociali” by Giuseppe Dossetti (1947 - 1951) (Italian Review of Legal History, 2024)
The paper focuses on the contribution of the editors of the journal “Cronache Sociali” to the identification of the personalist model as the basis of the new political and social order of republican Italy. Having noted that recent studies on the birth of republican institutions and on its architects are characterized by the prevalence attributed to the comparison between the experience data of the constituent period and that of today, the article considers the decisive references of the magazine’s founders to the thought of Jacques Maritain and that of Emmanuel Mounier. Evidence is then given to the existence of different personalist visions among the different political forces involved in the constituent phase of the Republic. This pluralism represents the fundamental and decisive element of the Constitution, thanks to which, until the 1990s, different models of civil society and political society have confronted each other, maintaining a reference, increasingly weak but persistent, to the personalist foundation. The subsequent period, up to today, is marked by the progressive affirmation of the individualist paradigm.
Keywords: Personalist models; Pluralism; Civil Society; Political Society; Italian Constitution; Individualism.